“Art, Colors, and Emotions” Treatment (ACE-t): A Pilot Study on the Efficacy of an Art-Based Intervention for People With Alzheimer’s Disease - Savazzi, Federica; Isernia, Sara; Farina, Elisabetta; Fioravanti, Raffaella; D’Amico, Alessandra; Saibene, Francesca Lea; Rabuffetti, Marco; Gilli, Gabriella; Alberoni, Margherita; Nemni, Raffaello; Baglio, Francesca (Frontiers in Psychology, 2020)
Increasing evidence suggests that non-pharmacological therapies impact on neuropsychiatric symptoms and quality of life in people with Alzheimer’s disease. Among these, art-based interventions seem particularly suitable for elders’ rehabilitation as they act both on cognitive functions and quality of life. However, their benefits are not yet appropriately explored. The main aim of this quasi-experimental study was to test the feasibility and likely efficacy of a novel multi-dimensional visual-art intervention for people with Alzheimer’s disease (PWAD), named Art, Colors, and Emotions treatment (ACE-t). A group of PWAD (N = 10) was recruited from the Memory Clinic of Don Gnocchi Foundation to take part in the ACE-t. A historical control group that followed a usual care program (N = 10) was used for comparison. We considered both feasibility outputs (adherence and acceptability) and efficacy outcome measures (neuropsychological and neurobehavioral scales). We observed a good adherence to and acceptability of the ACE-t. The following significant intervention-related changes were also observed in ACE-t with respect to usual care: improvement in general cognition assessed with Alzheimer’s Disease Assessment Scale–Cognitive, in language, and in executive functions, reduction in Neuropsychiatric Inventory scale score. In conclusion, ACE-t could be considered a suitable intervention for the rehabilitation of PWAD with positive effects on the cognitive and behavioral status. ACE is a promising new art-based intervention that merits further research, including confirmatory trials of our preliminary results.